L’arrêt Vavilov : à la recherche de l’équilibre perdu entre la primauté du droit et la suprématie législative - Popescu, Monica (Les Cahiers de droit, 2021)
Rendered in December 2019, the Vavilov decision sets the contemporary analytical framework for the judicial review of an administrative decision on the merits. On this occasion, the Supreme Court expressed the desire to add a certain degree of certainty and consistency to this field of law. This article focuses on the new approach’s propensity to achieve that goal. The analysis begins with the observation that there exists a connection between the instability that has historically characterized the law of judicial review and the failure of previous approaches to adequately guide reviewing courts in the fulfillment of their mission, which consists of balancing the rule of law and legislative supremacy. In light of earlier case law, the author concludes that the Vavilov decision offers the prospect of greater certainty in determining the applicable standard of review, but that the risk of instability remains with respect to the application of the reasonableness standard. Indeed, while the Supreme Court’s guidance in this regard generally reflects a concern to alleviate the tension underlying the relationship between rule of law and legislative supremacy principles, some of the majority justices’ assertions, namely that certain statutory provisions “relating to the scope of a decision maker’s authority” may involve only one interpretation, may weaken the self-discipline of reviewing courts on which judicial deference is based.